1985
DOI: 10.1136/oem.42.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole body vibration on biogenic amines in rat brain.

Abstract: The effects of whole body vibration on the concentrations of noradrenaline (NA), dopamine (DA), and serotonin (5-HT) in the whole brain and brain regions of rats were investigated. Compared with control rats, vibration with 20 Hz frequency decreased the brain concentration of NA only when the acceleration (intensity) was increased to 5.0 G (p less than 0.05). The concentration of DA in the whole brain was not affected by acceleration. When acceleration was kept at a constant 0.4 G level and rats were exposed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…According to some data [27], serotonin can exert direct excitatory effects via serotonin receptors of different subtypes localized on the surface of the neurons; at the same time, this agent realizes its inhibitory effects indirectly, by activation of local inhibitory GABA-ergic interneurons. Based on these data, we can suppose that the predominance of excitatory vibrational stimulation-induced effects in the hypothalamus (an increase in the mean discharge frequency, the respective shifts in the distribution of neurons within different frequency ranges, and alteration of the mean frequency of impulsation within separate frequency subgroups), which are clearly pronounced after 5 days of vibration sessions, is related to an increase in the concentration of serotonin in the hypothalamus [6].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…According to some data [27], serotonin can exert direct excitatory effects via serotonin receptors of different subtypes localized on the surface of the neurons; at the same time, this agent realizes its inhibitory effects indirectly, by activation of local inhibitory GABA-ergic interneurons. Based on these data, we can suppose that the predominance of excitatory vibrational stimulation-induced effects in the hypothalamus (an increase in the mean discharge frequency, the respective shifts in the distribution of neurons within different frequency ranges, and alteration of the mean frequency of impulsation within separate frequency subgroups), which are clearly pronounced after 5 days of vibration sessions, is related to an increase in the concentration of serotonin in the hypothalamus [6].…”
Section: Resultsmentioning
confidence: 98%
“…Activation of the cerebral GABA system is considered a modulatory mechanism that limits potentially dangerous excitation of the stress-realizing systems of the organism. It was demonstrated that vibrational stimulation provides generalized excitation of cerebral neuromodulatory systems [5,6,22]. Monoaminergic systems are known to regulate stress-induced neuroendocrine, autonomic, and behavioral reactions of the organism by controlling the information flow to neuronal networks [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All stress influences induce significant changes in the activity of the noradrenaline-, serotonin-, and dopaminergic systems in most subdivisions of the brain [3][4][5]15], which correlate with a significant rise in the corticosterone level in the blood plasma [2]. In different structural/functional cerebral systems, including the hypothalamus, reception of corticosterone undergoes considerable modifications after long-lasting vibrational stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies demonstrated that the action of general vibration is a stressor factor intensely influencing the organism of humans [1][2][3][4]. Vibration induces an imbalance of homeostasis, with the subsequent development of disorders of the functions of the nervous and endocrine systems and changes in the emotional state [5].…”
Section: Introductionmentioning
confidence: 99%